Pengaruh Model Problem Based Learning (PBL) Terhadap Kemampuan Pemecahan Masalah Matematis Peserta Didik kelas X SMA Negeri 1 Kabun - Auladina, Hafizah; Effendi, Leo Adhar (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2025)
The mathematics learning process requires students to develop strong problem-solving skills. However, at SMA Negeri 1 Kabun, these skills remain low due to teacher-centered learning and limited activities that foster independent thinking. This study aims to examine the effect of the Problem-Based Learning (PBL) model on the mathematical problem-solving skills of grade X students at SMA Negeri 1 Kabun. The research employed a quasi-experimental method with a Nonequivalent Control Group Design. The population included all grade X students in the 2025/2026 academic year. Samples were selected using a purposive sampling technique, with 34 students from class Xa as the experimental group and 32 students from class Xc as the control group. Research instruments consisted of validated problem-solving test sheets and learning tools. Data were collected through both test and non-test techniques, and analyzed using descriptive and inferential statistical methods. The findings show significant differences in the average mathematical problem-solving abilities between students in the experimental and control groups after receiving different treatments. Results of the Independent Sample T-Test indicate a significance value (sig. 2-tailed) of 0.000, which is lower than α = 0.05 (0.000 < 0.05). Thus, the null hypothesis is rejected, and the alternative hypothesis is accepted. This suggests that the implementation of the Problem-Based Learning (PBL) model has a positive effect on improving the mathematical problem-solving skills of grade X students at SMA Negeri 1 Kabun